Strategi Penekanan Tingginya Tingkat Anak Tidak Sekolah: Studi Kasus Desa Lebak, Kecamatan Grabag - Edwin Nurjaman; Dita Nur Kholifah Asilla; Eko Suherli; Latifah Furhatus Shalihah; Muhammad Ulin Nuha; Nur Azizah Chaeningrum; Yulius Prasetyo Herlambang; Rofika Adelia; Ataka Akhsya Sadat; Sekar Larasati; Beta Estri Adiana (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The problem of Out-of-School Children (OSC) in Lebak Village, Grabag Subdistrict, Magelang Regency, represents a complex educational issue that requires appropriate handling strategies. This study aims to analyze the factors influencing the high number of OSC while evaluating the strategies implemented by Universitas Tidar students through the Community Service Program (KKN) in addressing this challenge. The findings reveal three main causes of OSC: zoning, learning motivation, and local culture. The zoning factor is related to limited access to public schools due to distance, while low learning motivation emerges from the lack of family support. Cultural factors are reflected in parents’ tendency to prioritize religious education in traditional Islamic boarding schools that do not follow a formal curriculum, which results in children not receiving general education diplomas. The strategies applied by KKN students included socialization about the importance of education to both students and parents, installing learning schedule banners to build study discipline, and providing direct mentoring for children at risk of becoming OSC. This approach highlights the importance of collaboration among families, schools, communities, and the government in creating a supportive environment for children’s education. The outcomes of the program show an increase in community awareness regarding the importance of formal education and the emergence of renewed motivation among children to continue schooling. Thus, it can be concluded that the KKN strategies contributed positively to reducing the number of OSC and can serve as a sustainable model of community empowerment in the field of education.